Alterações morfofisiológicas renais em ratos wistar submetidos à má-nutrição intrauterina. - Thiago de Oliveira Assis; Thiago André Alves Fidelis (Acta Médica Portuguesa, 2011)
Many epidemiological studies suggest that the intra uterine environment is extremely important in determining the future of individual health. Changes in maternal nutritional status, reflected in birth weight may program the offspring to the development of diseases in adulthood. Studies with animals exposed to intrauterine malnutrition have suggested a reduction in the number of clusters in addition to increased blood pressure.To review the literature morphophysiology changes in the kidney of adult Wistar rats exposed to malnutrition during intrauterine life.We performed a search in the following databases: PubMed, MEDLINE, SCIENCE DIRECT, LILACS. The main search terms were malnutrition and renal function in Portuguese and English. We included original articles involving albino rats. We excluded review articles as well as those involving humans.According to Franco et al (2009) renal function and the number of glomeruli reduced by poor on intrauterine development, predisposing offspring to kidney disease in adulthood. According to Chen (2009) ultra-glomerular structure is not affected by maternal malnutrition suggesting that this factor does not contribute to the pathogenesis of hypertension after maternal malnutrition. Viana-son et al (2009) believes that stress on placents, causes disruption on sodium pumps in the proximal tubules of the kidney, resulting hypertension.The intrauterine malnutrition appears to interfere with the programming of kidney function with changes in glomerular morphophysiology, however, its mechanisms remain uncertain. We suggest further studies of the type and randomized clinical trials aimed at understanding the factors that trigger this process.